Sexual and reproductive health service utilization and associated factors among high school students in Ethiopia: systematic review and meta-analysis - Delie, Amare Mebrat; Adal, Ousman; Tareke, Abiyu Abadi; Ketema Bogale, Eyob; Anagaw, Tadele Fentabel; Tiruneh, Misganaw Guadie; Fenta, Eneyew Talie; Endeshaw, Destaw (Frontiers in Reproductive Health, 2024)
IntroductionSeveral studies have been done on the utilization of sexual and reproductive health services by high school students in Ethiopia, but they have yielded inconsistent results. This study aimed to evaluate the extent to which high school students in Ethiopia are using sexual and reproductive health services by conducting a systematic review and meta-analysis.MethodsVarious electronic databases such as PubMed, Cochrane Library, AJOL, Google Scholar, and Grey Literature were used to search for relevant articles. Preferred Reporting Items for Systematic Reviews and Meta-Analysis Guidelines were followed for this review and meta-analysis. Heterogeneity was assessed using I2 and Cochrane Q statistical tests, and data analysis was done with STATA 17 software. Random effect meta-analyses were used to determine the overall utilization rate of sexual and reproductive health services.ResultThis review included 20 studies with 12, 215 study participants. The pooled magnitude of sexual and reproductive health service utilization among high school students in Ethiopia was 29.79% (95% CI: 25.14, 34.43). Students with grades 11–12 (AOR = 2.33, 95% CI: 1.39, 3.90), aged between 20 and 24 years (AOR = 2.61; 95% CI: 1.79–3.81), having higher level of knowledge towards sexual and reproductive health issues (AOR = 3.10; 95% CI: 1.67–5.77), previous history of sexual intercourse (AOR = 4.18; 95% CI: 2.59–6.75), previous history of sexually transmitted infection (AOR = 3.74; 95% CI: 2.22–6.31), presence of a reproductive health service facility in the school (AOR = 2.55; 95% CI: 1.72–3.77), and ever-discussed reproductive health issues (AOR = 4.04; 95% CI: 1.62–10.03) were more likely to utilize sexual and reproductive health services.ConclusionsThe overall utilization of sexual and reproductive services among high school students in Ethiopia was found to be low as compared to SDG 3.7. Older individuals with higher education levels and knowledge about sexual and reproductive health services, as well as those who have had previous sexual experiences or discussions about sexual health, are more likely to utilize reproductive health services. To increase utilization, the Ministry of Health and the Ministry of Education should prioritize these factors.